Sutrikusios galūnių kraujagyslių raidos, vyraujant venų patologijai, diagnostika ir gydymas: 50 ligonių tyrimas - Triponis, Vytautas (Lietuvos chirurgija, 2005)
Vytautas Triponis Vilnius City University Hospital, Vascular Surgery Center, Antakalnio str. 57, LT-10207, Vilnius, Lithuania El paštas: vytautas.triponis@mf.vu.lt Background / Objective The rate of congenital vascular malformations is 1.5%. The aim of the study was to analyze clinical manifestations of predominantly venous congenital vascular malformations, to determine indication criteria for invasive treatment and to evaluate its preliminary results. Patients and methods There were 50 patients under observation. Symptoms and signs were assessed and their significance in the establishing of congenital vascular malformation diagnosis was evaluated. The following imaging procedures were made: ultrasound duplex scan in 29, arteriography in 15, phlebography in 19, MRA in 3, CTA in 4 patients, lymphography in 1 patient. Surgical treatment consisted of phlebectomy, ligation of the Marginal Vein branches, excision of deep extratruncular venous formations. 29 patients underwent surgical treatment, 14 patients were treated conservatively. Congenital vascular malformations were apportioned according to Hamburg Classification. Results The truncular form of the disease was present in 30 patients. The extratruncular form was determined in 20 cases. Phlebectasia alone was a sign in 20 patients. It was combined with other marks in 21 patients. Port-wine stain manifested in 17 (77.3%) patients. In 10 patients phlebectasia and in 22 port-wine stain were noticed as birthmarks. Venostasis decreased after operations in all patients. Excision of extratruncular dysplastic veins resulted in pain alleviation. In 9 patients the disease was taken for simple varicose veins by general surgeons and in 2 patients port-wine stain was misdiagnosed and excised causing cosmetic defects. Conclusions The history, symptoms and signs are essential for making the diagnosis of predominantly venous malformations. The correct method of treatment can be chosen on the background of vascular imaging. Surgery was the method of choice in this disease with progressing symptoms. Keywords: predominantly venous vascular malformation, symptoms and signs, vascular imaging, surgical treatment